Decreasing the coking and deactivation of a reforming Ni-Ce/Al2O3 catalyst with intraparticle SiC in hydrogen production routes. (1st April 2023) - Tavares, Fernanda; Mohamed, Hend O.; Kulkarni, Shekhar R.; Morlanés, Natalia; Castaño, Pedro
Graphical abstract: Highlights: Silicon carbide was successfully employed as co-support for Ni reforming catalyst. SiC controls the metal-support interaction and decreases the size of Ni. SiC indirectly enhances the catalyst performance and extends the lifetime. Coke formation was controlled significantly by adding SiC as support material. Abstract: Steam reforming processes are under pressure to fuel the hydrogen economy, cutting its significant carbon footprint and transitioning to renewable feedstock while improving catalyst performance and lifetime. A seemingly inert material such as silicon carbide (SiC, also known as carborundum), introduced in the catalytic particles, significantly influences catalytic performance and particularly the deactivation. We synthesized different catalysts with similar amounts of active materials (20 wt% of Ni and 2 wt% of Ce) and varied the proportion (0 to 78 wt%) and particle size (38 to 112 µm) of SiC within alumina. We used various techniques to characterize the catalysts and test them in reforming heptane, which was employed as a model molecule. The maximum enhancement with SiC occurs using 20 wt% of SiC with a size of 38 µm. Further, the enhancement with SiC is due to the control of the Ni particle size, leading to a 26 % improvement in the apparent reaction rate (per exposed Ni) and a 69 % decline in the deactivation rate compared to the SiC-free counterpart.